Physicochemical and organoleptic characteristics of halal carica (Carica pubescens) jelly candy with the addition of carica seed juice - Albana, Ridho Huda; Khairi, Amalya Nurul; Jebreen, Ali Mohammad Yousef (Journal of Halal Science and Research, 2025)
Carica fruit is a fruit of the same genus as papaya, but has a chewier and more compact texture and a more fragrant aroma when compared to papaya. Carica can increase the body’s immunity because the content of flavonoid compounds in carica is known to be higher than that of papaya. Carica seeds have antioxidant activity and have a high flavonoid content with a value of 55.6 mgQE/g, so they are beneficial for health. The addition of carica seed juice to carica jelly candy is expected to be able to add economic value and nutritional value to jelly candy. The purpose of this study is to determine the physicochemical and organoleptic properties of jelly candy. The method in the research was divided into three stages, namely making carica seed juice, making jelly candy formulations, and product analysis, including moisture content, ash content, pH, antioxidant, total flavonoids, texture, and organoleptic tests. This study used a Complete Random Design (CRD) with one factor of difference in the percentage of carica seed juice added in jelly candy, namely F0 (0% carica seed juice), F1 (32% carica seed juice), F2 (36% carica seed juice), and F3 (40% carica seed juice). Statistical analysis was carried out using one–way ANOVA followed by the Duncan Multiple Range Test (DMRT) at a confidence level og 95%. Jelly carica candy has moisture content value of 18.06% – 18.41%; ash content 1.35 – 1.85%; pH 4.6 – 5.3; antioxidant 928.69 – 1562.97 ppm; flavonoids 0.75 – 2.02 mgQE/g; hardness 61.01 – 141.70 N; cohesiveness 0.36 – 0.44; gumminess 28.37 – 62.45; springiness 0.76 – 0.83; chewiness 21.74 – 52.00; yellowish – orange color, distinctive carica flavor, chewy texture, non – sticky and has a sweet and sour taste. The addition of carica seed juice has a significant effect on the physicochemical and organoleptic properties of carica jelly candy. Keywords: Antioxidant, Carica jelly candy, Carica seed juice, Formulation, Physical properties, Total flavonoid.